Framing and Its Impact. An Analysis Based on the Example of Migration-related Discourse - Dargiewicz, Anna (Papers in Linguistics, 2020)
The aim of the present article is, rather than discussing individual theories of framing, an analysis of the phenomenon from the point of view of linguistics. Interpretative frame is interesting as a linguistic phenomenon resulting from linguistic activity and also because of the influence it has or can have on the addressee of the given linguistic activity, precisely due to its specific linguistic form. The empirical research on which this article is based (and which is connected with the discourse on migration-related problems) focuses on the interpretative frame, the lexical means employed to establish the frame, and the reactions that deliberate wording can evoke among the receivers. The theoretical reflections are justified by the description of the results of analysing the relevant research corpus.